Nurse’s Experiences in Implementing an Islamic Care Nursing Practice in Sharia-based Hospital Yogyakarta: A Phenomenological Study - Wardaningsih, Shanti; Junita, Aldina Puput (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Caring is the concept of a basic approach in nursing. It is an action that affects the level of satisfaction in hospitalized patients. Caring practice is very important for patient satisfaction. If it is in accordance with patient expectations, it will be considered as satisfying nursing services. However, in reality, there are still many nurses who have not shown caring practice toward patients and there may be some nurses who do not have time to listen to patients, provide comfort, or other caring actions. Nurses are considered to be noble professions as they are the people who take care and help the patients. The noble profession can be seen through the practice of the nurse such as caring actions which can improve patient satisfaction, especially Islamic caring, which is to include Islamic values in the hospital regardless of the patient’s status. AIM: This study aims to explore the experiences of nurses in implementing Islamic caring practices at the Islamic Hospital in Yogyakarta. METHODS: This study used a qualitative method with a phenomenological approach. The data collection conducted in this study was an in-depth interview method. The number of participants in this study was six nurses who worked at PKU Muhammadiyah Yogyakarta Hospital and Nur Hidayah Hospital, Yogyakarta. RESULTS: The results of this study showed four main themes regarding the experience of nurses in implementing Islamic caring practices at the Islamic Hospital in Yogyakarta. CONCLUSION: The four main themes are nurse’s spiritual experiences, sharia-based services, attitudes toward Islamic caring practices, and the support and the barrier in carrying out Islamic caring practices.